Talent Scouting Children's Swimming Sport in East Langsa District - Suandi Selian; Yoki Afriandy Rangkuti; Dodi Irwansyah; Jubaidah (Matondang Journal, 2022)
Bukit Meutuah Village, East Langsa District Langsa City is one of the villages that has the potential to contribute to gifted children because children are very fond of sports and have a high level of enthusiasm for sports activities. The location of the village is adjacent to a river that is often used by children to play and swim. However, with the existence of several existing facilities and infrastructure, the village has not been said to be fully accomplished in the field of sports both at the village and sub-district levels. This study aims to determine the swimming talent and potential of children aged 11-12 years in Bukit Meutuah Village, East Langsa District. This research was conducted by conducting a Talent Scouting Test with the Sport Search method which consisted of 10 test items which included height, weight, sitting height, arm span, throwing and catching tennis balls, throwing basketballs, jumping upright, running agility, sprinting 40 meters and multi-stage running. Sampling in this study used a total sampling technique, with quantitative descriptive research methods. Data analysis matched the test results obtained with the aptitude test scoring norm table and used percentages to describe the frequency and percentage obtained. The results showed that in the short distance swimming, all children as many as 25 people (100%) had no potential or were not talented to become candidates for short distance swimming athletes. While in long-distance swimming as many as 5 children (20%) have potential talent in long-distance swimming and as many as 20 children (80%) do not have potential or talent in long-distance swimming.